Conductive polymer based on spatially heterogeneous structure and reversible temperature-sensitive electrode thereof

CN122917286APending Publication Date: 2026-10-16WUHAN TEXTILE UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610972851.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]鉴于现有技术的上述缺陷,本发明的目的在于,提供一种基于空间异质结构的导电聚合物及其可逆温度敏感电极,解决单一聚合物在经历高温PTC转变后,侧链的集体剧烈运动会造成阴离子掺杂通道的不可逆堵塞,从而导致电阻难以恢复、PTC效应衰减的技术缺陷,并保持升降温循环工况下可逆的电阻增大与恢复特性,实现对锂离子电池的可逆热保护

Benefits of technology

本发明提供一种基于空间异质结构的导电聚合物及其制备方法,该导电聚合物具有空间异质结构,通过长侧链和短侧链这两种力学和物理特性截然不同的区域在纳米尺度上交替排列,形成周期性的局域链间强相互作用(短侧链区域)和局域空隙(长侧链区域),这种异质区边界影响区域中的相互作用耦合,是赋予材料可逆PTC效应的核心机制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917286A_ABST
    Figure CN122917286A_ABST
Patent Text Reader

Abstract

The application discloses a conductive polymer based on a spatial heterogeneous structure and a reversible temperature-sensitive electrode thereof, and belongs to the technical field of lithium ion batteries. The conductive polymer is constructed by constructing a spatial heterogeneous structure, and is endowed with unique reversible temperature-sensitive response characteristics. The temperature-sensitive electrode constructed based on the polymer breaks through the technical bottleneck that the existing system is generally irreversible in heat response. At a normal working temperature, the resistivity is small; at the resistivity change temperature (i.e. high temperature exceeding 100 DEG C), the resistivity sharply increases, and the heat closing feature is shown. Moreover, the polymer molecular chain structure can be kept relatively stable in multiple temperature rise and fall cycles, so that the reversible heat closing effect can be realized at the battery level, and the lithium ion battery can be constructed to be safer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a conductive polymer based on a spatial heterostructure and its reversible temperature-sensitive electrode. Background Technology

[0002] Driven by the global energy transition, the use of lithium-ion batteries in consumer electronics, electric vehicles, and other fields continues to increase. Particularly in the new energy vehicle market, the pursuit of longer driving range has fueled the rapid development of high-energy-density batteries. However, high energy density and high safety are often difficult to balance, and the safety issues of lithium-ion batteries remain a key bottleneck restricting their large-scale application.

[0003] Thermal runaway is the root cause of safety problems in lithium-ion batteries. When a battery is subjected to abuse conditions such as overcharging or internal short circuits, the battery temperature rises sharply. Once the temperature reaches the decomposition temperature of the solid electrolyte interphase (SEI) film, a series of exothermic chain reactions are triggered inside the battery, ultimately leading to fire and explosion.

[0004] To improve the intrinsic safety of lithium-ion batteries, many protection methods have been proposed. One promising strategy is to use electrodes with a positive temperature coefficient (PTC) to suppress electron conduction inside the battery under abuse conditions, thereby shutting down the battery reaction and achieving thermal protection for lithium-ion batteries.

[0005] The reason why conductive polymers exhibit the PTC effect is that at high temperatures, the chain segment movement of doped conductive polymers accelerates, leading to the dedoping of anions and thus causing the conductive polymer to lose its conductivity. The inventor's research team is dedicated to the research of reversible temperature-sensitive electrodes. For example, the research paper (Li Hui. Conductive polymer PTC materials and their application in thermal protection of lithium-ion batteries [D]. Wuhan: Wuhan University, 2020.) studied poly(3-alkylthiophene)s (P3ATs) and discussed the structure-property relationship and temperature response mechanism. This paper used poly(3-dodecylthiophene-2,5-diyl) (P3DDT) coatings to construct temperature-sensitive electrodes, with a resistance switching temperature range of approximately 90~100 °C and a resistance-to-weight ratio of approximately four orders of magnitude. Furthermore, the research article (Chen, H., Miao, S., Li, H., Cao, Y., Ai, X. and Fang, Y. (2025), Molecular Engineering of Poly(3-Alkylthiophene)swith Enhanced Positive Temperature Coefficient Effects for Intrinsically Safe Lithium-Ion Batteries. ChemSusChem, 18: e202500398.) investigated the effects of long alkyl side chains (C 14~18 P3ATs and anion dopant PF6 - TFSI - ClO4 - The effect of PTC switching temperature on the resistance ratio was investigated, and the temperature-sensitive electrode achieved turn-off at approximately 110 °C. A separate research article (H. Chen, H. Wang, S. Miao, et al. “Temperature-Responsive Electrodes Enabled by Poly(3-Alkylthiophene)s with Tailored Branches.” Adv. Sustainable Syst.9, no. 12 (2025): e01198.) studied the relationship between branched P3ATs and temperature-responsive electrodes and thermal protection, discussing the influence of different anions on the PTC switching temperature and resistance ratio. This temperature-sensitive electrode achieved turn-off at approximately 100 °C.

[0006] However, existing reports on conductive polymer-based PTC electrodes for battery thermal shutdown typically demonstrate a one-time event. Once the battery triggers thermal protection, the change in conductivity is usually irreversible, exhibiting irreversible thermal shutdown characteristics. The root cause of this irreversibility lies in the fact that long-chain polymers undergo intense thermal motion in their side chains at high temperatures, leading to the collapse and blockage of doped channels after anion dedoping. After cooling, the anions are difficult to reintegrate, resulting in poor resistance recovery and a decay of the PTC effect. Shorter side chains, due to their lower vibrational energy, tend to weaken the PTC effect, thus failing to demonstrate reversible battery thermal shutdown. For example, the PTC intensities of poly(3-decylthiophene) after three temperature cycles were 2.57, 1.64, and 0.83, respectively, while those of poly(3-ethylthiophene) after two temperature cycles were 1.91 and 0.66, respectively. This is the underlying mechanism preventing existing technologies from achieving a reliable and reversible PTC effect. In terms of process, irreversible thermal response behavior also brings hidden dangers in actual manufacturing. Since electrode preparation usually requires a high-temperature drying step, this heat treatment may trigger the thermal protection mechanism in advance, causing the electrode to shut down before it is put into use. Such irreversible thermal response behavior further limits its application. Summary of the Invention

[0007] In view of the above-mentioned defects of the prior art, the purpose of the present invention is to provide a conductive polymer based on a spatial heterostructure and its reversible temperature-sensitive electrode, which solves the technical defect that the collective violent movement of the side chains of a single polymer after undergoing a high-temperature PTC transformation will cause irreversible blockage of the anion doping channel, resulting in the resistance being difficult to recover and the PTC effect decaying, and maintains the reversible resistance increase and recovery characteristics under temperature rise and fall cycle conditions, thereby achieving reversible thermal protection for lithium-ion batteries.

[0008] To achieve the above objectives, the technical solution provided by the present invention is as follows: In a first aspect of the invention, a conductive polymer based on a spatial heterostructure is provided, said conductive polymer being a polythiophene compound formed by copolymerization of a long-side-chain thiophene monomer and a short-side-chain thiophene monomer; wherein the side chain substitution positions of the long-side-chain thiophene monomer and the short-side-chain thiophene monomer are each independently at the 3-position or the 3,4-position of the thiophene ring; wherein in the long-side-chain thiophene monomer, the long side chain is C 6~16 Alkyl groups; in short-chain thiophene monomers, the short side chain is C. 1~4 Alkyl groups; the molar ratio of long-chain thiophene monomers to short-chain thiophene monomers is 1:0.2~1.

[0009] Based on the substitution sites, substituent chain lengths, and ratios under the above design conditions, the conductive polymer forms a heterogeneous region with spatially distinct mechanical and physical properties through the periodic inter-chain interactions and local voids of the molecular chain formed by the long and short side chains of the monomer.

[0010] Preferably, the long side chain is selected from hydroxyl, heptyl, octyl, nonyl, decyl, dodecyl, tetradecyl, and hexadecyl; and the short side chain is selected from methyl, ethyl, propyl, and butyl.

[0011] Preferably, when the side chain substitution positions of the long-side-chain thiophene monomer or the short-side-chain thiophene monomer are each independently at the 3rd and 4th positions of the thiophene ring, the group types of the 3rd and 4th position side chains are consistent.

[0012] Preferably, the conductive polymer has a resistance increase ratio ≥2 at a resistance switching temperature of 90~160 °C, and retains reversible resistance increase and recovery characteristics after at least 3 heating and cooling cycles.

[0013] In a second aspect of the present invention, a method for preparing a conductive polymer based on a spatial heterostructure, as described in the first aspect of the present invention, is provided, comprising the following steps: According to the specified ratio, long-side-chain thiophene monomers and short-side-chain thiophene monomers are dissolved in a solvent, an oxidant is added, and the reaction is carried out under an inert atmosphere; after the reaction is completed, the product is collected and purified to obtain a conductive polymer.

[0014] Preferably, the total amount of the long-side-chain thiophene monomer and the short-side-chain thiophene monomer accounts for 0.5 wt.% to 5 wt.% of the solvent.

[0015] Preferably, the solvent includes at least one of water, methanol, chloroform, and acetonitrile; the oxidant includes at least one of ferric chloride, perchloric acid, and ammonium persulfate, and the amount of oxidant used is 1 to 10 times the total mass of the long-chain thiophene monomer and the short-chain thiophene monomer.

[0016] Preferably, the reaction temperature is -20~25 ℃ and the reaction time is 0.5~24 h.

[0017] In a third aspect of the invention, a reversible temperature-sensitive electrode is provided, comprising: Active material layer and current collector; The active material layer includes a conductive polymer, an electrode active material, a binder, and a conductive agent, as described in the first aspect of this invention.

[0018] Preferably, in the active material layer, the content of the conductive polymer is 0.5 wt.% to 5 wt.%, the content of the electrode active material is 80 wt.% to 95 wt.%, the content of the binder is 1 wt.% to 10 wt.%, and the content of the conductive agent is 1 wt.% to 10 wt.%.

[0019] Preferably, the conductive polymer is doped with a dopant, which includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium chloride, and lithium nitrate.

[0020] Preferably, the electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese cobalt ternary composite material, lithium iron phosphate, and graphite.

[0021] Preferably, the adhesive comprises at least one of polytetrafluoroethylene, polyacrylic acid, styrene-butadiene rubber, and polyvinylidene fluoride.

[0022] Preferably, the conductive material includes at least one of conductive carbon black, conductive graphite, Ketjen black, and acetylene black.

[0023] Preferably, the current collector comprises aluminum foil or copper foil.

[0024] In the preparation process of this invention, a conductive polymer based on a spatial heterostructure is prepared by chemical oxidative polymerization. The obtained polymer is coated on the surface of the current collector for modification. The resulting conductive polymer based on a spatial heterostructure and its reversible temperature-sensitive electrode exhibit reliable reversible thermal protection behavior, thereby achieving reversible thermal protection for lithium-ion batteries.

[0025] The reversible temperature-sensitive electrode prepared by the above method exhibits a dramatic increase in resistance and conductivity by more than three orders of magnitude at temperatures exceeding 100 °C, resulting in near-zero electrochemical capacity and demonstrating thermal shutdown characteristics, thereby suppressing thermal runaway. After returning to room temperature, the electrode can still be charged normally. After at least three heating and cooling cycles, it still exhibits excellent PTC effect, demonstrating reversible thermal protection behavior. Furthermore, at normal operating temperatures, the electrochemical performance of this reversible temperature-sensitive electrode is essentially consistent with that of conventional electrodes, demonstrating significant application potential.

[0026] Based on the above technical solutions, the design concept and principle of this invention are as follows: This invention offers a novel design approach beyond traditional methods for optimizing single polymers. By mixing long and short chains, it specifically constructs a polymer composite system with heterogeneous spatial structures. The invention designs a mixture of long-side-chain polythiophene and short-side-chain polythiophene, utilizing the differentiated movement behaviors of the two chains at high temperatures to create spatial heterogeneity at the aggregation level that is not present in single polymers.

[0027] Spatially heterogeneous structures consist of spatially distinct regions with different mechanical and / or physical properties. Compared to homogeneous materials, rationally designed heterogeneous structures can exhibit superior overall performance. However, the inventors are aware that not all heterogeneous structures can significantly improve material properties, requiring a deeper understanding of structure-property relationships and the interaction mechanisms between regions. Based on this understanding, this invention constructs spatially distinct heterogeneous structures within conductive polymer molecular chains through the synergistic design of long and short side chains, using 3- or 3,4-position substituted polythiophene. The long side-chain regions provide higher flexibility and PTC response, and their thermal motion is key to driving anion demonstration and achieving a high lift-to-drag ratio. The short side-chain regions, on the other hand, possess higher stereoregularity and main-chain rigidity, playing a structural support and steric hindrance role in the system, preventing excessive entanglement of the long chains. These two regions with distinctly different mechanical and physical properties alternate at the nanoscale, forming periodic strong inter-chain interactions (short side-chain regions) and local voids (long side-chain regions). This interaction coupling within the heterogeneous region boundary is the core mechanism that endows the material with a reversible PTC effect.

[0028] Based on the above system design, under operating conditions, the long and short side chains in the polymer each perform different and irreplaceable functions, achieving a highly reversible PTC effect through synergistic action. Specifically, the long-chain side chains undergo drastic conformational changes and creep during heating, acting as the main contributors to effectively depurifying anions and generating a high lift-to-drag ratio, thus serving as reversible temperature-sensitive switches. The short-chain side chains, due to their weaker mobility, play a role in structural support and steric hindrance within the system. When the long chains undergo thermal motion at high temperatures and may block ion transport channels, the rigid short chains physically maintain the necessary free volume and nanochannels, thereby reserving a pathway for the re-intercalation of anions after cooling and ensuring channel recovery. Through this collaborative design, where the long chains are responsible for switching and the short chains ensure channel recovery, the composite material simultaneously achieves properties that a single polymer system cannot simultaneously possess: a high lift-to-drag ratio and high reversibility.

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects: This invention provides a conductive polymer based on a spatial heterostructure and its preparation method. The conductive polymer has a spatial heterostructure in which two regions with distinctly different mechanical and physical properties, long side chains and short side chains, are alternately arranged at the nanoscale to form periodic strong inter-chain interactions (short side chain regions) and local voids (long side chain regions). This interaction coupling in the heterogeneous region boundary is the core mechanism that endows the material with the reversible PTC effect.

[0030] This invention provides a reversible temperature-sensitive electrode comprising a conductive polymer based on a spatial heterostructure. In application, compared to a blank battery, the room temperature cycling performance and rate discharge performance of the conductive polymer and the reversible temperature-sensitive electrode are essentially the same. At resistive switching temperature, the resistivity increases sharply, causing the electrode to change from a conductive state to an insulating state, cutting off electron transport within the battery. When the temperature returns to room temperature, the conductivity recovers. The conductive polymer and its reversible temperature-sensitive electrode exhibit a reversible PTC effect, maintaining reversible resistance increase and recovery characteristics after at least three temperature cycles, achieving reversible thermal protection for lithium-ion batteries, greatly improving safety, and further expanding practical applications. Attached Figure Description

[0031] Figure 1 The infrared spectrum of the conductive polymer (reversible temperature-sensitive material) of Example 1 of the present invention is shown. Figure 2 This is a curve showing the change in conductivity of the conductive polymer with temperature in Example 1 of the present invention; Figure 3 The PTC intensity curve of the conductive polymer in Example 1 of this invention; Figure 4 The thermogravimetry (TG) curve of the conductive polymer in Example 1 of this invention; Figure 5 This is a discharge capacity diagram of the reversible temperature-sensitive electrode during thermal cycling in Embodiment 1 of the present invention; Figure 6 The diagram shows the room temperature cycling performance of the reversible temperature-sensitive electrode in Embodiment 1 of the present invention. Figure 7 This is a diagram showing the rate discharge performance of the reversible temperature-sensitive electrode in Embodiment 1 of the present invention. Detailed Implementation

[0032] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0033] Example 1 This embodiment provides conductive polymers prepared using 3-ethylthiophene and 3-decylthiophene as long-chain and short-chain thiophene monomers, respectively, as reversible temperature-sensitive materials for reversible temperature-sensitive electrodes, and assembled into coin cells for actual operating condition testing. The steps are as follows: (1) Preparation of reversible temperature-sensitive materials: 8 g of ferric chloride was weighed and dissolved in 50 mL of deionized water. The mixture was magnetically stirred for 30 min under inert nitrogen atmosphere. Then, 5 g of 3-ethylthiophene and 3-decylthiophene (molar ratio 1:0.75, total) were weighed and dissolved in 100 mL of deionized water. The mixture was added dropwise to the reaction system of the above step and magnetically stirred at 5 °C for 8 h. Then, 500 mL of deionized water was added and the mixture was stirred at room temperature for 24 h to remove excess ferric chloride. The mixture was separated using a separatory funnel and washed repeatedly until the upper layer was colorless. Solvent molecules were removed by rotary evaporation and then dried in a vacuum drying oven at 60 °C for 12 h to obtain product 1.

[0034] (2) Fabrication of reversible temperature-sensitive electrode: Product 1 was dissolved in acetonitrile with a mass fraction of 0.5 wt.%, and then the solution was coated onto an aluminum foil current collector, allowing the solvent to evaporate. Lithium iron phosphate (LiFePO4) was selected as the active material, polytetrafluoroethylene (PTFE) as the binder, and acetylene black as the conductive agent. These three materials were ground for 1 h, with mass fractions of 85 wt.%, 5 wt.%, and 10 wt.%, respectively. The ground slurry was then coated onto the modified aluminum foil and dried in a vacuum drying oven at 45 ℃ for 8 h to obtain the reversible temperature-sensitive electrode.

[0035] (3) Assembly of button cells: The electrode was cut into 12 mm diameter discs, with lithium metal as the counter electrode and the electrolyte being a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) containing 1 mol / L lithium hexafluorophosphate (LiPF6) (EC:DEC=1:1, v / v). The CR2032 coin cell was then assembled.

[0036] Example 2 This embodiment is basically the same as Embodiment 1, except that the molar ratio of 3-ethylthiophene and 3-decylthiophene in this embodiment is 1:0.2, while the parameters of the other steps remain the same.

[0037] Example 3 This embodiment is basically the same as Embodiment 1, except that the molar ratio of 3-ethylthiophene and 3-decylthiophene in this embodiment is 1:0.5, while the parameters of the other steps remain the same.

[0038] Example 4 This embodiment is basically the same as Embodiment 1, except that 3,4-ethylthiophene and 3,4-decylthiophene are used in this embodiment with a molar ratio of 1:0.75, the stirring time is 10 h, and the reaction temperature is 10 ℃. The parameters of the remaining steps are the same.

[0039] Example 5 This embodiment is basically the same as Embodiment 1, except that 3-methylthiophene and 3-hexylthiophene are used in this embodiment, with a molar ratio of 1:0.75, a mass fraction of 1 wt.% in the solvent, a stirring time of 10 h, conductive carbon black as the conductive agent, and a reaction temperature of 10 ℃. The parameters of the remaining steps are the same.

[0040] Example 6 This embodiment is basically the same as Embodiment 1, except that 3-butylthiophene and 3-heptylthiophene are used in this embodiment with a molar ratio of 1:0.6, the stirring time is 12 h, the binder is polyvinylidene fluoride, and the conductive agent is conductive carbon black. The parameters of the remaining steps are the same.

[0041] Example 7 This embodiment is basically the same as Embodiment 1, except that 3,4-butylthiophene and 3,4-heptylthiophene are used in this embodiment with a molar ratio of 1:0.8, the stirring time is 12 h, the binder is polyvinylidene fluoride, and the conductive agent is conductive carbon black. The parameters of the remaining steps are the same.

[0042] Example 8 This embodiment is basically the same as Embodiment 1, except that 3-butylthiophene and 3-decylthiophene are used in this embodiment, the solvent is acetonitrile, the molar ratio is 1:0.9, the mass fraction of the solvent is 1 wt.%, the stirring time is 10 h, the binder is polyvinylidene fluoride, and the conductive agent is conductive carbon black. The parameters of the remaining steps are the same.

[0043] Example 9 This embodiment is basically the same as Embodiment 1, except that 3-methylthiophene and 3-dodecylthiophene are used in this embodiment, acetonitrile is used as the solvent, the molar ratio is 1:0.5, the reaction temperature is 15 ℃, the stirring time is 10 h, and lithium cobalt oxide is used as the active material. The parameters of the remaining steps are the same.

[0044] Example 10 This embodiment is basically the same as Embodiment 1, except that 3-ethylthiophene and 3,4-dodecylthiophene are used in this embodiment, acetonitrile is used as the solvent, the molar ratio is 1:0.2, the mass fraction of the solvent is 0.6 wt.%, the reaction temperature is -5 ℃, the stirring time is 12 h, and lithium cobalt oxide is used as the active material. The parameters of the remaining steps are the same.

[0045] Example 11 This embodiment is basically the same as Embodiment 1, except that 3,4-ethylthiophene and 3-dodecylthiophene are used in this embodiment, chloroform is used as the solvent, the molar ratio is 1:0.4, the mass fraction of the solvent is 0.7 wt.%, the reaction temperature is -10℃, the stirring time is 12 h, and lithium cobalt oxide is used as the active material. The parameters of the remaining steps are the same.

[0046] Example 12 This embodiment is basically the same as Embodiment 1, except that 3,4-butylthiophene and 3,4-tetradecylthiophene are used in this embodiment, the solvent is chloroform, the molar ratio is 1:1, the mass fraction of the solvent is 0.8 wt.%, the reaction temperature is -20℃, the stirring time is 24 h, and the active material is lithium manganese oxide. The parameters of the remaining steps are the same.

[0047] Example 13 This embodiment is basically the same as Embodiment 1, except that 3-ethylthiophene and 3-decylthiophene are used in this embodiment, ethanol is used as the solvent, the stirring time is 24 h, and lithium manganese oxide is used as the active material. The other steps and parameters are the same.

[0048] Example 14 This embodiment is basically the same as Embodiment 1, except that in the preparation process of the reversible temperature-sensitive electrode in this embodiment, the solvent is ethanol, the current collector is copper foil current collector, the active material is graphite, and the binder is polyacrylic acid, while the parameters of the remaining steps remain the same.

[0049] Example 15 This embodiment is basically the same as Embodiment 1, except that the molar ratio is 1:0.2, the stirring time is 10 h, the current collector is copper foil, the active material is graphite, and the binder is polyacrylic acid. The parameters of the remaining steps are the same.

[0050] Example 16 This embodiment is basically the same as Embodiment 1, except that 3-butylthiophene and hexadecylthiophene are used in this embodiment, acetonitrile is used as the solvent, the molar ratio is 1:0.5, the mass fraction of the solvent is 0.6 wt.%, the reaction temperature is -20 ℃, the current collector is copper foil, the active material is graphite, and the binder is polyacrylic acid. The parameters of the remaining steps are the same.

[0051] Comparative Example 1 This comparative example provides a lithium-ion coin cell that does not use a reversible temperature-sensitive electrode, which is prepared according to the following method: (1) Electrode preparation: The active material is LiFePO4, the binder is polytetrafluoroethylene, and the conductive agent is acetylene black. These three materials are ground for 1 hour, and their mass components are 85 wt.%, 5 wt.%, and 10 wt.%, respectively. The ground slurry is then coated onto aluminum foil and dried in a vacuum drying oven at 100 ℃ for 12 hours.

[0052] (2) Assembly of button cells: The electrode was cut into 12 mm diameter discs, with lithium metal as the counter electrode and a 1 M LiPF6 / EC:DEC (1:1, v / v) electrolyte solution to assemble a CR2032 coin cell.

[0053] Comparative Example 2 This comparative example provides a lithium-ion coin cell that does not use a reversible temperature-sensitive electrode, which is prepared according to the following method: (1) Electrode preparation: The active material is graphite, the binder is polyacrylic acid, and the conductive agent is acetylene black. These three materials are ground for 1 hour, and their mass components are 85 wt.%, 5 wt.%, and 10 wt.%, respectively. The ground slurry is then coated onto copper foil and dried in a vacuum drying oven at 100 ℃ for 12 hours.

[0054] (2) Assembly of button cells: The electrode was cut into 12 mm diameter discs, with lithium metal as the counter electrode and a 1 M LiPF6 / EC:DEC (1:1, v / v) electrolyte solution to assemble a CR2032 coin cell.

[0055] The parameter settings in this embodiment of the invention are shown in Table 1.

[0056] Table 1: Fabrication Parameters of Conductive Polymer Materials and Reversible Temperature Sensing Electrodes

[0057] The above parameters and raw material selections can all be used to prepare the target conductive polymer material and reversible temperature-sensitive electrode. Those skilled in the art can also select from the preferred parameters within the range of this invention, based on actual conditions or needs, to achieve the preparation of the conductive polymer material and reversible temperature-sensitive electrode.

[0058] Using Example 1 as a representative embodiment of the present invention, the conductive polymer material in Example 1 was characterized by infrared spectroscopy, and its infrared spectrum is shown below. Figure 1 As shown. Figure 1 The display shows 2920 cm. -1 2850 cm -1 1376 cm -1The characteristic peaks at 1510 cm⁻¹ represent the stretching and bending vibrations of the side-chain alkyl groups, respectively. -1 1465 cm -1 1057 cm -1 825 cm -1 The characteristic peaks at the locations are the antisymmetric and symmetric stretching vibrations of the C=C double bond on the thiophene ring, as well as the in-plane and out-of-plane deformation vibrations, which confirm the presence of the target product.

[0059] Figure 2 The graph shows the conductivity of the conductive polymer material in Example 1 as a function of temperature. Specifically, the resistivity at room temperature is 6.06 × 10⁻⁶. 4 The resistivity is 5.87 × 10⁻⁶ Ω·cm when the temperature rises to 100 °C. 7 The resistivity is approximately 3 orders of magnitude Ω·cm, exhibiting excellent PTC effect; after the 8th thermal cycle, the PTC effect is still strong, indicating that Example 1 has a reliable reversible PTC effect.

[0060] Figure 3 The PTC intensity curves for the conductive polymer material in Example 1 are shown. The PTC intensities of this material in the first, third, fifth, seventh, and eighth tests are 2.99, 2.9, 2.8, 1.81, and 1.74, respectively. These results also demonstrate that Example 1 exhibits a reliable reversible PTC effect.

[0061] The thermal stability of the conductive polymer of Example 1 was tested by thermogravimetric analysis in a nitrogen atmosphere at a heating rate of 10 °C / min. -1 The temperature range is 25~800℃. The results are as follows... Figure 4 As shown, no significant weight loss was observed in Example 1 before the temperature rose to 400 °C, demonstrating that Example 1 can maintain structural stability over a wide temperature range.

[0062] Figure 5 The figure shows the discharge capacity of the reversible temperature-sensitive electrode in Example 1 during thermal cycling. As can be seen from the figure, the battery can hardly release any capacity when discharged at 100 °C. After cooling to room temperature, the battery can still be charged normally. Even during the 5th thermal cycle, it still has an excellent PTC effect, indicating that the thermal shutdown behavior of the battery is highly reversible.

[0063] Figure 6 The cycling performance of the electrodes of Example 1 and Comparative Example 1 at 0.5 C at room temperature was compared. As can be seen from the figure, after 200 charge-discharge cycles, Example 1 and Comparative Example 1 exhibited almost the same discharge specific capacity and capacity retention, with capacity retention of 95% and 97%, respectively.

[0064] Figure 7 The specific capacity of the electrodes of Example 1 and Comparative Example 1 at different discharge rates at room temperature was compared. As can be seen from the figure, when the discharge rate increases from 0.1 C to 0.5 C and 1 C, the specific capacity of Example 1 increases from 155 mA·h·g. -1 Slowly decreased to 142 mA·h·g -1 and 138 mA·h·g -1 Even at a high rate of 2 C, Example 1 still maintains 127 mA·h·g. -1 The specific capacity of Comparative Example 1 demonstrates excellent high-rate performance. In comparison, the specific capacities of Comparative Example 1 at 0.1 C, 0.5 C, 1 C, and 2 C are 156 mA·h·g. -1 145 mA·h·g -1 141 mA·h·g -1 and 130 mA·h·g -1 .

[0065] The lithium-ion coin cells obtained in Examples 2 to 16 of this invention were subjected to reversible PTC effect, TG test, thermal cycling discharge capacity test, room temperature cycling performance and rate discharge performance test respectively, according to the method described in Example 1. The results show that when the obtained reversible temperature-sensitive electrode is used to prepare lithium-ion coin cells, it can exhibit excellent reversible PTC effect, thermal stability, room temperature cycling performance and rate discharge performance.

[0066] In summary, the reversible temperature-sensitive electrode provided by this invention, when applied to lithium-ion batteries, not only has good thermal stability, room temperature cycling performance and rate discharge performance, but also achieves reversible thermal protection for lithium-ion batteries.

[0067] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. A conductive polymer based on a spatial heterostructure, characterized in that: The conductive polymer is a polythiophene compound formed by copolymerization of long-side-chain thiophene monomers and short-side-chain thiophene monomers; the side chain substitution positions of the long-side-chain thiophene monomers and the short-side-chain thiophene monomers are each independently at the 3-position or 3,4-position of the thiophene ring; in the long-side-chain thiophene monomer, the long side chain is C 6~16 Alkyl groups; in short-chain thiophene monomers, the short side chain is C. 1~4 Alkyl groups; the molar ratio of long-chain thiophene monomers to short-chain thiophene monomers is 1:0.2~1.

2. The conductive polymer based on a spatial heterostructure according to claim 1, characterized in that: The long side chain is selected from hydroxyl, heptyl, octyl, nonyl, decyl, dodecyl, tetradecyl, and hexadecyl; the short side chain is selected from methyl, ethyl, propyl, and butyl.

3. The conductive polymer based on a spatial heterostructure according to claim 1, characterized in that: When the side chain substitution positions of the long-side-chain thiophene monomer or the short-side-chain thiophene monomer are each independently at the 3 and 4 positions of the thiophene ring, the group types of the 3-position side chain and the 4-position side chain are consistent.

4. The conductive polymer based on a spatial heterostructure according to claim 1, characterized in that: The conductive polymer exhibits a resistance increase ratio ≥2 at a resistance switching temperature of 90~160 °C, and retains reversible resistance increase and recovery characteristics after at least 3 heating and cooling cycles.

5. A method for preparing a conductive polymer based on a spatial heterostructure as described in any one of claims 1 to 4, characterized in that, Includes the following steps: According to the specified ratio, long-side-chain thiophene monomers and short-side-chain thiophene monomers are dissolved in a solvent, an oxidant is added, and the reaction is carried out under an inert atmosphere; after the reaction is completed, the product is collected and purified to obtain a conductive polymer.

6. The method for preparing the conductive polymer based on a spatial heterostructure according to claim 5, characterized in that: The total amount of long-chain thiophene monomers and short-chain thiophene monomers in the solvent is 0.5 wt.% to 5 wt.%; the solvent includes at least one of water, methanol, chloroform, and acetonitrile; the oxidant includes at least one of ferric chloride, perchloric acid, and ammonium persulfate, and the amount of oxidant used is 1 to 10 times the total mass of long-chain thiophene monomers and short-chain thiophene monomers.

7. The method for preparing the conductive polymer based on a spatial heterostructure according to claim 5, characterized in that: The reaction temperature is -20~25 ℃, and the reaction time is 0.5~24 h.

8. A reversible temperature-sensitive electrode, characterized in that, include: An active material layer and a current collector; the active material layer comprises a conductive polymer based on a spatial heterostructure, an electrode active material, a binder, and a conductive agent as described in any one of claims 1 to 4.

9. The reversible temperature-sensitive electrode according to claim 8, characterized in that: In the active material layer, the content of conductive polymer is 0.5 wt.%~5 wt.%, the content of electrode active material is 80 wt.%~95 wt.%, the content of binder is 1 wt.%~10 wt.%, and the content of conductive agent is 1 wt.%~10 wt.%.

10. The reversible temperature-sensitive electrode according to claim 8, characterized in that: The conductive polymer is doped with a dopant, which includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium chloride, and lithium nitrate; the electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese cobalt ternary composite material, lithium iron phosphate, and graphite; the binder includes at least one of polytetrafluoroethylene, polyacrylic acid, styrene-butadiene rubber, and polyvinylidene fluoride; the conductive material includes at least one of conductive carbon black, conductive graphite, Ketjen black, and acetylene black; and the current collector includes aluminum foil or copper foil.